Utilization of Local Food Resources through the Empowerment of Posyandu Cadres in Sorghum-Fish Nugget Production to Support the Supplementary Feeding Program - Grouse Oematan; Marselinus Laga Nur; Mega Liufeto; Utma Aspatria; Gustaf Oematan; Yeni Haning (Yayasan Sumber Daya Manusia Cerdas, 2026)
Nutritional problems among children under five remain a concern in Rote Barat Laut District, while local food resources such as sorghum and fish have not yet been optimally utilized in community-based food processing. This community service program aimed to strengthen the practical capacity of Posyandu cadres to utilize local food resources through the production of sorghum-fish nuggets to support supplementary feeding activities (Pemberian Makanan Tambahan or PMT). The program involved 30 participants, consisting of 15 Posyandu cadres and 15 mothers of children under five, and included a needs assessment, nutrition education, production demonstrations and hands-on practice, packaging, distribution, and an introduction to basic marketing. Pretests and posttests were administered as part of the formative evaluation. Following supervised practical sessions, all 15 cadres completed the main production and packaging stages during the simulation session, as documented through direct observation by the implementation team. The activity produced 100 nuggets, which were divided into 20 packages and distributed through mothers or caregivers to 20 children under five registered at the Posyandu. A cadre-based group was also initiated as an initial platform for follow-up production and marketing activities. The program demonstrated the preliminary feasibility of practice-based training for promoting the utilization of local food resources. However, further evaluation is required regarding formulation standardization, nutritional content, food safety, acceptability, and post-program sustainability.